2020
DOI: 10.1123/ijspp.2018-0527
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Immune and Nutritional Biomarkers on Illness Risk During Interval Training

Abstract: Intensive training periods may negatively influence immune function, but the immunological consequences of specific high-intensity-training (HIT) prescriptions are not well defined. Purpose: To explore whether 3 different HIT prescriptions influence multiple health-related biomarkers and whether biomarker responses to HIT were associated with upper-respiratory-illness (URI) risk. Methods: Twenty-five male cyclists and triathletes were randomized to 3 HIT groups and completed 12 HIT sessions over 4 wk. Peak oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Indeed, a recent review of the complex relationship between nutrition and immune tolerance/resistance has recently proposed that energy restriction per se may not increase illness risk, and that previous associations reported in studies of athletic populations may be mediated by a common co-morbidity such as higher ratings of psychological stress [100]. Indeed, one study has reported an apparent disconnect between EA and the occurrence of upper respiratory infections in athletes who commenced high-intensity interval training [101]. Further research on this theme is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent review of the complex relationship between nutrition and immune tolerance/resistance has recently proposed that energy restriction per se may not increase illness risk, and that previous associations reported in studies of athletic populations may be mediated by a common co-morbidity such as higher ratings of psychological stress [100]. Indeed, one study has reported an apparent disconnect between EA and the occurrence of upper respiratory infections in athletes who commenced high-intensity interval training [101]. Further research on this theme is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…There was some evidence of increased risk of ARill and ARinf in endurance athletes and runners specifically. There was a lower risk of prolonged ARill (symptom days) for elite athletes 27–29. One study hypothesised that the individual training load threshold, above which the risk of illness increases,30 is lower in national level athletes than in international athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some strategies might be used to alleviate this responses, like to reduce the duration of the sprints to less than 15 s [ 95 , 96 , 97 ], reduce the number of sprints [ 95 , 98 ], increase rest duration and perform active rest between sprints [ 99 ] or reduce weekly training frequency [ 100 ]. Moreover, caution should be taken with training schedule and weekly volume since consecutive days of two daily IT sessions induce acute immunosuppression and increased risk for infection [ 101 , 102 ].…”
Section: Interval Training and Immunitymentioning
confidence: 99%